Design and implementation of improved sliding mode control for electric vehicle voltage stabilization. (2021) - Mathankumar, M.; Viswanathan, Tamilarasu; Balachander, K.; Suryaprakash, S.
Abstract: This paper presents a novel improved sliding mode control technique for Electric Vehicle (EV) voltage stabilization. The deprived operation of EV charging results in variation of voltages that leads to degraded load performance. In other way, the distributed energy sources consequences in distressing the designed EV models. This process must normalize through appropriate use of controller which is capable of refining current and voltage in the complete structure. Various disturbances regarding load dissimilarity in the scheme comprehend over the control with trivial voltage variation study for less than 1 s. The different constraints such as speed, load current and voltage, looping restrictions are reserved into interpretation for finest enactment. The simulation results show that the voltage is stabilized than existing arrangements through negligible adaptation in the strategy to match the mathematical design. The proposed arrangement shows the stabilized voltage output and significantly diminish the inclusive cost.